Multivariate analysis of resistance components of the saccharin and biomass sorghum to Ramulispora sorghi - M. A. S. Castrillon (Scientific Electronic Archives, 2020)
The objective of this work was to evaluate the reaction of biomass and saccharin sorghum genotypes to a isolate of the Ramulispora sorghi. The experiment was conducted in a completely randomized design with three replications in a greenhouse. The variables analyzed were: area below the disease curve progress; lesion length (LL), lesions width (LW); normalized area below the curve of the lesion area expansion; incubation period and latency period. Data were submitted to analysis of variance, Pearson correlation and multivariate analysis based on Mahalanobis distance, using the Tocher and UPGMA clustering method. Significant differences were observed in the level of (p<0.01) and (p<0.05), for almost all variables analyzed. Of the 45 correlations, only 22 (48.89%) were significant by t-test, regardless of significance (p<0.01 or 0.05), where it was observed that in all significant correlations were positive, indicating that the reaction symptoms correlate between the variables evaluated. The groupings generated by the Tocher and UPGMA clustering method were in agreement to group genotypes with the same behavior in relation to reaction to Ramulispora sorghi. From the observed results, it was verified that all evaluated genotypes presented ramulispora spot symptoms, thus demonstrating their susceptibility to the pathogen.